PENGARUH SELF LEADERSHIP, MOTIVASI, DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PT TIRTA INVESTAMA KABUPATEN BADUNG - I Gusti Bagus Dony Manggala S; I Gede Rihayana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The aim of this study was to analyze the impact of self-leadership, motivation, and self-efficacy on employee performance. The population under investigation consisted of employees at PT Tirta Investama. The sample for this study comprised 86 respondents, selected through simple random sampling. A questionnaire was utilized to collect primary data from the 86 respondents. The research employed regression analysis to ascertain the influence of self-leadership, motivation, and self-efficacy on employee performance. The results, derived from multiple linear regression analysis, revealed several significant findings. The T-test indicated that self-leadership has a positive effect on employee performance, as evidenced by a coefficient value of 0.210 and a significance level of 0.007, which is below the threshold of 0.05. Motivation similarly demonstrated a positive and significant impact on employee performance, with a coefficient value of 0.260 and a significance level of 0.000, below the 0.05 threshold. Additionally, self- efficacy exhibited a positive and significant effect, supported by a coefficient value of 0.276 and a significance level of 0.000, below the 0.05 threshold. These findings underscore the importance of self- leadership, motivation, and self-efficacy in enhancing employee performance within the context of PT Tirta Investama.